Genetic gain of grain yield and quality in bread wheat cultivars representing 40 years of breeding in Morocco - S. Bennani; M. Taghouti; F. Gaboun (Труды по прикладной ботанике, генетике и селекции)
Background. Knowledge about the genetic gain for fundamental traits over time is essential for a critical assessment and improvement of breeding programs, especially regarding staple crops like bread wheat.Materials and methods. To estimate the genetic gain in bread wheat breeding in Morocco, grain yield (GY) and grain protein content (GPC) data were collected from 12 multi-environment field trials for 20 bread wheat cultivars released between 1980 and 2022.Results and discussion. Analysis of variance highlighted a high significant variability between environments (E), cultivars (G), and a significant G × E interaction (P < 0.001). Based on stability analysis, the modern cultivars released during the two last decades (2002–2012 and 2013–2022) showed the highest performances and wider stability than old ones, especially in low-yielding environments. Genetic gain (GG) for GY was 21.4 kg ha−1 yr−1 (0.75% yr–1) over 4 decades of breeding. This progress was declining when advancing in decades and ranged from 11% (from 1980–1990 to 1991–2001) to less than 7% (from 2002–2012 to 2013–2022). The GG in low and intermediate yielding environments were the most important (17.34% and 6.88% yr–1 respectively), while GG was nonsignificant in high-yielding environments (4.62% yr–1). Within the same period, GPC showed a nonsignificant negative trend of –0.007% (–0.002% yr–1), while derivative parameters from GY and GPC indicated high positive genetic progress. More efforts should be deployed to implement a good balance between yield performance and quality in the new released cultivars despite the negative correlation between these two traits (r = –0.36; P < 0.001).Conclusion. Adopting advanced technologies, like genomic selection, adequate agronomic practices, and more efficient selection criteria are essential steps to further increase simultaneously grain yield and quality traits.